2010
DOI: 10.1161/atvbaha.110.213702
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Functionally Active P2Y12 ADP Receptors by Thrombin in Human Smooth Muscle Cells and the Presence of P2Y12 in Carotid Artery Lesions

Abstract: Objective-The platelet P2Y12 ADP receptor is a well-known target of thienopyridine-type antiplatelet drugs. This study is the first to describe increased transcriptional expression of a functionally active P2Y12 in response to thrombin in human vascular smooth muscle cells (SMC). Methods and Results-On exposure to thrombin, P2Y12 mRNA was transiently increased, whereas total protein and cell surface expression of P2Y12 were markedly increased within 6 hours and remained elevated over 24 hours. This effect was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…In cultured human vascular smooth muscle cells pretreated with thrombin, the agonist 2-methylthio-ADP induced mitogenic effects by an action on P2Y 12 receptors [50]. In agreement with these findings, 2-methylthio-ADP also increased the proliferation of cultured human coronary smooth muscle cells in our present experiments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In cultured human vascular smooth muscle cells pretreated with thrombin, the agonist 2-methylthio-ADP induced mitogenic effects by an action on P2Y 12 receptors [50]. In agreement with these findings, 2-methylthio-ADP also increased the proliferation of cultured human coronary smooth muscle cells in our present experiments.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the inhibition of proliferation due to the activation of P2X 1 receptors as observed in the present study, P2Y receptor subtypes including P2Y 2 , P2Y 6 , and P2Y 12 receptors mediate increases in proliferation of vascular smooth muscle cells [5,11,29,30,[46][47][48][49][50][51]. In cultured human vascular smooth muscle cells pretreated with thrombin, the agonist 2-methylthio-ADP induced mitogenic effects by an action on P2Y 12 receptors [50].…”
Section: Discussioncontrasting
confidence: 75%
“…12 More recently, several studies showed that P2Y12 is also expressed in vascular SMCs. 23,24 We examined the expression levels of P2Y12 in platelets, peripheral white blood cells (WBC), and aortic SMCs using quantitative real-time reverse transcription polymerase chain reaction to confirm the expression of P2Y12 in SMCs and evaluate P2Y12 expression in nonplatelet white cells. The results were unambiguous, and they demonstrated a much weaker expression of P2Y12 in aortic SMCs than in platelets (≈7% of P2Y12 level in platelets), and almost no expression of P2Y12 in peripheral blood white cells (≈0.5% of P2Y12 level in platelets; Figure II in the online-only Data Supplement).…”
Section: P2y12 In Platelets Contributes To Atherogenesismentioning
confidence: 99%
“…Nevertheless, we provided substantial evidence which indicates that P2Y 12 may contribute to the progression of atherosclerosis at least in part by enhancing VSMCs migration from media to intima. Of note, in the study of Rauch et al, 10 direct stimulation of P2Y 12 receptor by its agonist 2-MeSADP did not increase human VSMCs proliferation. DNA synthesis was significantly enhanced only when 2-MeSADP was added after preincubation of cells with thrombin for 6 hours.…”
mentioning
confidence: 83%